Symbolic consumption and the social construction of product characteristics - Ulrich Witt (Max Planck Institute of Economics, 2008)
As recognized since long, consumption serving to signal social status, group membership, or self-esteem is a socially contingent activity. The corresponding expenditures are motivated mainly by the symbolic value they have for transmitting the signal. However, this presupposes some form of social coordination on what are valid, approved symbols. Unlike consumption not serving signaling purposes, the technological characteristics of the goods and services consumed may be secondary what counts is their socially agreed capacity to function as a symbol. The paper discusses in detail the cognitive underpinnings of social agreement on consumption symbols and a model of their spontaneous emergence.
Keywords: 330